Quality and Use of Mobile Applications for Transportation Service: Influence on Satisfaction - Preciado-Ortiz, Claudia Leticia (Mercados y Negocios, 2021)
The main objective of this research work was to analyze the factors that influence satisfaction and the intention to continue using mobile transport applications in young university students from Guadalajara, Jalisco, Mexico. The approach was quantitative. 144 valid responses were used, and partial least squares structural equation modeling (PLS-SEM) was used to test the model. The software employing was the SmartPLS 3. The results indicate that the quality of the design, the quality of the information and the quality of the system are predictors of influence on satisfaction. Companies that offer individual passenger transport through a mobile application have increased in recent years, generating strong competition both between existing brands and with established traditional taxis. This study provides new and recent information for marketing managers and academics on application user behavior in the transportation industry.